Global pipelines and absorptive capacity: insights from the clustered firms at são francisco river valley (2020)
This study verified if the knowledge provides by global pipelines is absorbed by clustered firms contributes to minimising both local and clusters asymmetries. We studied one of the most important agricultural barns of Brazil, the fruit-growing cluster São Francisco River Valley (SFRV). It was a Case Study using the technique of Content Analysis through the ATLAS.ti software. A threefold data collection process enhanced the construct validity, allowing the triangulation of the sources and findings. The results showed that Global pipelines minimised the knowledge asymmetries among regions (macro level), but increase the asymmetries inside the cluster, among the firms (micro level). There are two mediating variables to increase the cluster innovation, the firm absorptive capacity and the information access. In the empirical level, the results showed that manager consultants are an essential figure in the SFRV, they are innovation hunters from global markets and provided the knowledge transfer to clustered firms.